Application of modified quartz crystal sensors: Detection of isobutyl alcohol, ethyl acetate and ethylene - Juncai, Hou; Yaohua, Hu; Kangquan, Guo (International Journal of Agricultural and Biological Engineering, 2014)
Aroma volatilization is one of the very important attributes of agricultural products during ripening. Ingredients of aroma compounds experience changes over products’ different ripening stages. This paper aimed to develop a detection system based on modified quartz crystal sensors to detect volatile organic compounds (VOCs). By drop-coating on sensors’ surface, four sensors were made using quartz crystal resonators coated with four different absorbable materials: ethyl cellulose, cellulose acetate, 1,2-dioleoyl-sn-glycero-3-[phosphor-L-serine], and galactosyl ceramide. With the diversely coated sensors, three VOCs: isobutyl alcohol, ethyl acetate and ethylene were detected at ppm level. To investigate the structure influence of the coated sensing films on VOCs absorption, the topography of films was imaged in 3D using atomic force microscopy (AFM) in tap mode for qualitative analysis of gas absorption. The selectivity and sensitivity were investigated when sensors were exposed to VOCs with increasing concentrations. The results showed that the frequency shift of sensors was linear to the concentrations of all three VOCs in the range of 5–25 ppm. With values reaching over 4.5 Hz/ppm, the sensitivity of cellulose acetate coated sensor to three VOCs was similar, higher than that of sensors with other coatings. The high sensitivity of the cellulose acetate coated sensor might be due to the film’s rough surface and porous structure. The results may help further research on detection of fruits’ organic volatiles during the ripening stage. Keywords: quartz crystal sensor, atomic force microscopy, detection, selectivity, sensitivity, volatile organic compounds DOI: 10.3965/j.ijabe.20140705.008 Citation: Hou J C, Hu Y H, Guo K Q. Application of modified quartz crystal sensors: detection of isobutyl alcohol, ethyl acetate and ethylene. Int J Agric & Biol Eng, 2014; 7(5): 71－77.